Mass Transfer Effects on Mixed Convective MHD Flow of Second Grade Fluid Past a Vertical Infinite Plate with Viscous Dissipation and Joule Heating - Swain, Bharat Keshari; Barik, Rabi Narayan (Journal of Institute of Science and Technology, 2022)
An attempt is made to study an unsteady, two-dimensional, laminar, mixed convective Magnetohydrodynamic (MHD) flow of an incompressible visco-elastic fluid (Waltersfluid model) past an infinite vertical plate. The reduced governing equations are solved analytically using two-term harmonic and non-harmonic functions. The effects of different pertinent parameters are discussed with the help of graphs and tables. The novelty of the present study is to account for the effects of viscous and joules dissipative heat and a linear first-order chemical reaction of diffusive species and mixed convective flow phenomena on an infinite vertical plate subjected to time-dependent suction velocity and a transverse magnetic field acting at a distance. The important findings reported herein are: increasing values of chemical reaction parameter cause low velocity and concentration, a decline in concentration profile is seen for the higher values of Schmidt number, Prandtl number contributes to more active convection. The application of the present study may be seen in combustion systems, nuclear reactors, and chemical processes. Before concluding the considered problem, our results are validated with previous results and are found to be in good agreement.